Efficacy and safety of bright light therapy for manic and depressive symptoms in patients with bipolar disorder: A systematic review and meta‐analysis. Issue 4 (10th February 2020) - Takeshima, Masahiro; Utsumi, Tomohiro; Aoki, Yumi; Wang, Zhe; Suzuki, Masahiro; Okajima, Isa; Watanabe, Norio; Watanabe, Koichiro; Takaesu, Yoshikazu
Abstract : Aim: This systematic review and meta‐analysis evaluated whether bright light therapy (BLT) is an effective and safe treatment for manic/depressive symptoms and a preventive measure for recurrent mood episodes in patients with bipolar disorder. Methods: A literature search of major electronic databases was conducted in June 2019, including all published articles up to that date. Two researchers independently selected relevant publications, extracted data, and evaluated methodological quality according to the Cochrane criteria. Results: Six randomized controlled trials (RCT) evaluated the efficacy of BLT for bipolar depression. A meta‐analysis found no significant differences between BLT and placebo for the following outcomes: (i) rates of remission from depressive episodes (risk ratio [RR]: 1.81, 95% confidence interval [CI]: 0.43 to 7.64, P = 0.42); (ii) depressive symptom scores (standardized mean difference: −0.25, 95%CI: −0.74 to 0.23, P = 0.30); and (iii) rates of manic switching (RR: 1.00, 95%CI: 0.28 to 3.59, P = 0.26). The sensitivity analysis for studies with low overall indirectness did show a significant antidepressant effect for BLT (RR: 3.09, 95%CI: 1.62 to 5.90, P = 0.006). No RCT investigated the effect of BLT in preventing the recurrence of mood episodes in the euthymic state or in improving manic symptoms in the manic state. No severe adverse events were reported. Conclusion: While a meta‐analysis was unable to demonstrate the efficacy of BLT for bipolar depression, a sensitivity analysis did show a significant effect. Further well‐designed studies are needed to clarify the effectiveness of BLT, not only for the depressive state but also for other states, in the treatment of bipolar disorder.